Evaluation of surface properties of erythrocyte membranes in liver diseases - Maksane, Shalini Nitin; Guhasarkar, Shruti; Banerjee, Rinti; Dandekar, Sucheta Prakash (International Journal of Research in Medical Sciences, 2017)
Background: The physicochemical properties of Red Blood Cell membranes (RBC) are altered in liver diseases. Langmuir monolayers offer an excellent model system to study biological membrane surface properties. The aim of this study was to evaluate surface properties of erythrocyte membranes in liver diseases. Methods: Sixty-one patients with various liver diseases and fifteen controls were enrolled. Surface properties of RBC membrane were evaluated using Langmuir monolayers. Surface pressure area isotherms were recorded at body temperature using RBC membrane lipid extract. Student’s t-test and Analysis of variance tests were performed. Results: Mean maximum surface pressure and hysteresis area were significantly higher in cirrhotic and non-cirrhotic liver disease groups compared to controls. Within cirrhotics, mean maximum surface pressure and lift off area was significantly lower in the Child C group as compared to the Child A, B and A-B groups. The mean hysteresis area was significantly lower in the Child C group as compared to the Child B and A-B groups. Conclusion: The results of our study confirmed high rigidity of RBC membrane in mild and moderate liver cirrhosis and high fluidity in severe liver cirrhosis. This study may pave the way to the development of a surface activity based biophysical tool for therapeutic implication in liver diseases.